A targeted antibody-based array reveals a serum protein signature as biomarker for adolescent idiopathic scoliosis patients - Shao, Zhenxuan; Zhang, Zengjie; Tu, Yiting; Huang, Chongan; Chen, Liang; Sun, Anna; Sheng, Sunren; Zhang, Xiaolei; Wu, Yan (BMC genomics, 2023)
Evident adolescent idiopathic scoliosis (AIS) incurs high treatment costs, low quality of life, and many complications. Early screening of AIS is essential to avoid progressing to an evident stage. However, there is no valid serum biomarker for AIS for early screening. Antibody-based array is a large-scale study of proteins, which is expected to reveal a serum protein signature as biomarker for AIS. There are two segments of the research, including biomarkers screening and validation. In the biomarkers screening group, a total of 16 volunteers participated in this study, and we carried out differentially expressed proteins screening via protein array assay between No-AIS group and the AIS group, through which GeneSet enrichment analysis was performed. In the validation group with a total of 62 volunteers, the differentially expressed proteins from screening group were verified by Enzyme-Linked immunosorbent assay (ELISA), and then multiple regression analysis. In our study, there were twenty-nine differentially expressed proteins in AIS, through Protein array assay and GeneSet enrichment analysis in the biomarkers screening group. Then the expression of FAP, CD23 and B2M decreased as the degree of AIS increased via ELISA in validation group (FAP, p < 0.0001; CD23, p = 0.0002; B2M, p < 0.0001). Further, the results of multiple regression analysis showed that FAP, CD23 are linked to Cobb angle, whereas B2M were excluded because of multicollinearity. Altogether, we found that serum protein FAP and CD23 are intimately related to AIS, suggesting FAP and CD23 are expected to serve as the serum biomarkers, which significantly facilitate frequent longitudinal monitoring as to keep track of disease progression and tailor treatment accordingly.